Effects of spatangoid heart urchins on O-2 supply into coastal sediment - Vopel, K; Vopel, A; Thistle, D; Hancock, N (Inter-Research, 2007)
Spatangoid heart urchins are key bioturbators in the marine environment. They pump seawater from the sediment surface around their tests and, at the same time, constantly displace the surrounding sediment. To improve our understanding of the effects of this activity on the oxygenation of coastal sediment, we studied for the first time in situ [O-2] around Echinocardium cordatum at sub-millimeter resolution under different hydraulic conditions. In the laboratory, we investigated the effects of E. cordatum on pore-water pH and sediment apparent diffusivity. Individuals advancing 1 to 3 cm h(-1) through the upper 4 cm of the sediment displaced a greater volume of seawater than sediment per unit time. The O-2 uptake of the sediment surrounding E. cordatum was at least twice the respiration of the echinoids. Besides creating additional sediment contact with oxygenated seawater, E. cordatum affected the Supply of O-2 to the sediment by altering photosynthetic O-2 production at the sediment surface, and increasing the exchange area of the sediment-seawater interface and apparent diffusivity of the uppermost sediment layer. After the passage of an individual, pore-water [O-2] profiles indicative of benthic photosynthesis recovered rapidly from the disturbance, but the pH of deeper pore water was altered. In situ, time series measurements of [O-2] and hydrostatic pressure indicated that wind waves can increase the transport of O-2 across both the sediment-seawater interface and the interface between the seawater surrounding E. cordatum and the adjacent sediment.
Keywords: Bioturbation; Bioirrigation; Microphytobenthos; Benthic photosynthesis; Diffusion; Advection; Waves; Dissolved oxygen; Apparent diffusivity